5G Fixed Wireless Access for rural broadband - Eleni Laitsou; Nikos Ioannou; Dimitris Katsianis (International Telecommunications Society (ITS), 2022)
Mobile communication technology is moving into the fifth generation (5G) which is expected to overcome the new challenges that have emerged with the Internet of Things (IoT) and the exponential growth in demand for traffic [1], [2], [3]. The advent of 5G is allowing mobile technology to intersect with the demands of fixed line services. With fixed wireless access (FWA), network operators can provide ultra-fast broadband to suburbs and rural areas to support home and business applications where fiber installation and maintenance is very expensive. In this paper a techno-economic study is performed to assess the feasibility of the deployment of a 5G Standalone fixed wireless access network in a rural area. 24 European countries are taken as case studies. In each of these cases, the conditions are studied under which such an investment can be economically viable through increased revenues and reduced costs. The findings of this study can be an important tool for decision/policy makers in investment strategies for rural broadband networks and for the European Commission that has launched a targeted public consultation on a proposed revision of the Guidelines on State aid rules for broadband networks, 5g fixed wireless access networks included.
Keywords: 330; 5G fixed wireless access network; techno-economic evaluation; TONIC model; rural area; Net Present Value; Internal Rate of Return; Payback year; CAPEX